(untitled) (Kinesiology, 2022)
The aim of this study was to analyze the effect of different supplementation conditions on fatigue and performance in flywheel half-squat tests in senior men. Sixteen active males (age: 22.8±4.9 years; body mass index: 23.7±2.4 kg*m-2) participated in the intervention during a 4-week period. Four experimental conditions were established using a double-blind design: placebo, caffeine (CAF), beetroot juice (BRJ), and combined BRJ+CAF. To assess the effect of supplementation, participants completed a countermovement jump (CMJ) before (Pre), 30 s after (Post-30s) and 180 s after (Post-180 s) completing a flywheel half-squat exercise protocol (four sets of eight all-out repetitions, with a 3-min inter-set rest, using different inertial loads). Additionally, the mean power output during the flywheel half-squat protocol was recorded. A repeated measures ANOVA showed greater mean power ( 1000 W, p<.001) produced in flywheel exercise after the CAF, BRJ and BRJ+CAF consumption compared to the placebo condition. After placebo, CAF and BRJ, CMJ performance at Post-180 s was reduced compared to Pre (p=.003-.087, two-way ANOVA; ES=-0.39/-0.49), although no significant performance reduction (p=.087) was noted after BRJ+CAF. In conclusion, compared to placebo, CAF, BRJ, and BRJ+CAF allow greater total mean power in the flywheel half-squat power test, although without effects on exercise-related fatigue. Additionally, BRJ+CAF improved recovery after a high demanding power-production protocol. Key words: nutritional ergogenic aids, athletic performance, plyometric exercise, muscle fatigue, resistance training